Comparison Between Efficacy and Safety of Oral Azithromycin (250mg) vs Oral Doxycycline (100mg) in Treatment of Meibomian Gland Dysfunction (MGD) - Yousuf, Waseem; Humayun, Fakhar; Janjua, Teyyeb Azeem; Khan, Taimoor Ashraf; Sarfraz, Muhammad Haroon; Mehboob, Mohammad Asim (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the efficacy and safety of oral Azithromycin with oral Doxycycline in patients with Meibomian Gland Dysfunction.Study Design: Quasi-experimental study.Place and Duration of the Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Apr 2021 to Apr 2022.Methodology: The sample population comprised 172 subjects, including 86 cases in the oral Doxycycline-Group and 86 oralAzithromycin-Group. Meibomian Gland Dysfunction was diagnosed by a consultant ophthalmologist by slit-lampexamination. Schirmer-I test and Tear Break Up Time were performed. Signs and symptoms of Meibomian Gland Dysfunction were assessed before treatment and at six months follow-up.Results: The study recruited equal numbers of cases and controls. Symptoms scores for burning sensation (2.04±0.5 vs 1.9±0.7) and foreign body sensation (1.8±0.6 vs 1.5±0.8) were significantly higher in patients taking Doxycycline as compared to the Azithromycin-Group (p